Coordinated Allocation of Dispersed Reactive Power Resources for Voltage Regulation and Loss Minimization - O. Idris, Abdelrahman; Shareef, Hussain; N. Khalid, S.; M. Islam, Md.; Akbar, Siddiqul; A. Alkhatib, Ashwaq (International Journal of Engineering and Technology, 2019)
The major problems faced by utility companies are to provide standard voltage levels and to minimize system power losses. This paper introduces a coordinated allocation of multiple distributed reactive energy resources to regulate system voltage and minimize power losses. For this purpose sensitivity study is used to determine the appropriate location for placing distributed reactive energy resources and thereby reduce the search. The Al-Ain power distribution network (AADN) is considered as a real-world case study. For the AADN under investigation, a suitable objective function is formulated to lessen the installation cost and electric power losses. The problem is resolved by using the tabu search optimization method and DIgSILENT PowerFactory simulation software. Results depict that the proposed method can minimize system electric power losses and improve voltage regulation.Â Â